An electronic platform for real-time detection of bovine serum albumin by means of amine-functionalized zinc oxide microwires. Issue 2 (22nd December 2015) - Sanginario, Alessandro; Cauda, Valentina; Bonanno, Alberto; Bejtka, Katarzyna; Sapienza, Stefano; Demarchi, Danilo
Abstract : We report the fabrication of a customized electronic platform for biosensing, integrating a single functionalized microwire between two gold microelectrodes as a sensing element, including a custom microelectronic chip for signal readout. Abstract : We report the fabrication of a customized electronic platform for biosensing, integrating a single functionalized microwire between gold microelectrodes as a sensing element, including a custom microelectronic chip for signal readout. As a proof-of-concept, the platform was validated for the real-time detection of Bovine Serum Albumin (BSA) binding onto an NH2 -functionalized zinc oxide (ZnO-NH2 ) microwire. The ZnO-NH2 microwires were deposited between two gold electrodes by means of a dielectrophoresis (DEP) technique. A Quasi-Digital Impedance Converter (QDIC) was conceived to constantly and instantaneously readout ZnO microwire impedance and transfer data to a laptop. Microelectrodes, a QDIC, a DEP generator, and data analysis were integrated in a stacked-card PCB configuration for a better noise reduction and usability. The system was able to distinguish between different BSA concentrations and to give real-time information about the binding process.